Conversão catalítica de cetonas em 1,1-diidroperóxidos e tentativas de obtenção de 1,2,4,5-tetraoxanos potencialmente herbicidas - Almodevar Filipe Baldaia Silva (2015)
Cyclic peroxides have aroused the interest of many research groups due to their wide range of biological activities. Among these compounds 1,2,4,5-tetraoxanes have shown potent herbicidal activity. Therefore, we sought to enhance the activity of the known herbicide, 2-(1H-indol-3-yl) acetic acid, by introducing the endoperoxide function into its structure. There are many methods to synthesize 1,2,4,5-tetraoxanes nevertheless, the most general is the condensation reaction between 1,1-dihydroperoxides with ketones and aldehydes catalyzed by acids. Furthermore these synthesis methods commonly show several problems, such as formation of byproducts and low product yields. Thus, the first goal of this work was to develop an effective and reproducible methodology for the synthesis of 1,2,4,5-tetraoxanes, which could enable to obtain these products in a high yield. To achieve this, were evaluated in the 1,1-dihydroperoxides synthesis factors such as influence of water, type and concentration of catalysts and last, type of solvents. The use of 10 mol% of boron trifluoride etherate (BF3yEt2O) and 20 mol% of tin chloride (SnCl2) resulted in obtaining 1,1-diidroperoxydes in a higher yield, 77% and 73%, respectively. The best solvent for this reaction was found to be tetrahydrofuran. After optimization of the conditions for the preparation of 1,1-diidroperoxydes, the work was focused on its convertion into assymetric 1,2,4,5 –tetraoxanes. For this step the effect of different catalysts and their concentration were evaluated. We found that best results were obtained by the use of 100 mol% of Lucas reagent (ZnCl2-HCl and 50mol% of boron trifluoride etherate (BF3yEt2O) in dichloromethane. Under such conditions the products were obtained in yields of 30 % and 26%, respectively.Finally an attempt to synthesize a derivative of 2-(1H-indol-3-yl)acetic acid, by introducing a 1,2,4,5-tetraoxane unit into this compound was made, but time precluded the completion of this part of the work.